2021
DOI: 10.3390/jcm10143053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Exercise Capacity and Pulmonary Function in Post-COVID-19 Competitive Athletes

Abstract: Background: Limited evidence exists regarding adverse modifications affecting cardiovascular and pulmonary function in physical active adults affected by COVID-19, especially in athletic populations. We aimed to describe the clinical presentation of COVID-19 in a cohort of competitive athletes, as well as spirometry and echocardiography findings and cardio-respiratory performance during exercise. Methods: Twenty-four competitive athletes with COVID-19 were recruited for this study after ending self-isolation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 38 publications
11
63
0
Order By: Relevance
“…Moreover, no association between days of infection and ΔFVC, ΔFEV 1 , ΔFEV 1 /FVC, and ΔPEF was observed, even though the small sample size tested ( n = 10) and a narrow range of both dependent and independent variables may have hindered some associations. These findings suggest that COVID‐19 does not considerably affect FVC, FEV 1 , FEV 1 /FVC, and PEF in athletes with mild symptoms, which is in line with previous investigations (Fikenzer et al, 2021 ; Milovancev et al, 2021 ), but in contrast with others (Gervasi et al, 2021 ; Komici et al, 2021 ). No evidence of spirometric impairments was also observed in a large cohort of healthy young adults who had mild‐to‐moderate COVID‐19 symptoms (Mogensen et al, 2022 ), suggesting that spirometric impairments would unlikely occur in young and healthy populations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, no association between days of infection and ΔFVC, ΔFEV 1 , ΔFEV 1 /FVC, and ΔPEF was observed, even though the small sample size tested ( n = 10) and a narrow range of both dependent and independent variables may have hindered some associations. These findings suggest that COVID‐19 does not considerably affect FVC, FEV 1 , FEV 1 /FVC, and PEF in athletes with mild symptoms, which is in line with previous investigations (Fikenzer et al, 2021 ; Milovancev et al, 2021 ), but in contrast with others (Gervasi et al, 2021 ; Komici et al, 2021 ). No evidence of spirometric impairments was also observed in a large cohort of healthy young adults who had mild‐to‐moderate COVID‐19 symptoms (Mogensen et al, 2022 ), suggesting that spirometric impairments would unlikely occur in young and healthy populations.…”
Section: Discussionsupporting
confidence: 91%
“…There is limited and contradictory data on the effect of COVID‐19 on pulmonary function in the athletes population. Specifically, some studies have reported impairments in some of the spirometry measures tested following COVID‐19 (Fikenzer et al, 2021 ; Komici et al, 2021 ; Milovancev et al, 2021 ), while others have not (Gervasi et al, 2021 ; Komici et al, 2021 ). Different factors may have accounted for such discrepancies including, different types of research design used and athletes’ fitness level (Fikenzer et al, 2021 ; Gervasi et al, 2021 ; Komici et al, 2021 ; Milovancev et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we cannot delineate if the higher prevalence of abnormal spirometry in post-COVID as compared with reference athletes was due to COVID-19 or reflects baseline differences between the groups despite careful matching. Others have reported mild decreases in FEV 1 in athlete cohorts that were not selected for persistent symptoms as compared with pre-COVID values 15 or controls, 16 which support the possibility that the observed spirometry abnormalities in our study were due to COVID-19. Given incomplete longitudinal improvement, our study may have been enriched for athletes with mild baseline spirometry abnormalities, and future work should identify if such athletes are at higher risk of developing persistent cardiopulmonary symptoms after COVID-19 or if this represents a limitation of our small cohort size.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the presence of prominent symptoms, most athletes in our cohort did not demonstrate significant abnormalities of ventilatory efficiency or pVO 2 on their first CPET, which is consistent with others’ results in variably symptomatic athletes. 16 17 20 22 Conversely, we observed a high proportion of post-COVID athletes with mild abnormalities in screening spirometry. Our study is limited in that baseline pre-COVID spirometry was not available and, with a focus on ruling out cardiac disease, full and appropriately customised pulmonary evaluation was not systematically performed.…”
Section: Discussionmentioning
confidence: 62%